Robust polymer incorporated TiO2‐ZrO2 microsphere coatings by electrospraying technique with excellent and durable self cleaning, antibacterial and photocatalytic functionalities. Issue 34 (23rd April 2021) - Simon, Sanu Mathew; George, Gejo; Chandran, Anoop; Valparambil, Prakashan; M. Shamsudeen, Sajna; Saritha, A. C.; Biju, P. R.; Thomas, Sabu; Joseph, Cyriac; Vishwambharan, Unnikrishnan N.
Abstract: The applications of self‐cleaning coatings on large scale are limited due to their poor durability, remnants of hazardous by‐products and lack of biocompatibility. We propose to solve this problem by developing TiO2 ‐ZrO2 composite‐based self cleaning coatings. In order to achieve this task another important aspect was to select biocompatible polymers poly (methyl methacrylate) and pluronic F‐127 (PF‐127) as they can enhance the self‐cleaning capability of TiO2 ‐ZrO2 which itself is biocompatible and endowed with anti‐bacterial capability. The selection of a preparation technique that could produce coatings mimicking the nature has also been important and hence Electrospraying technique was selected as the processing method. The samples were then characterized using various techniques like field emission scanning electron microscopy, X‐ray diffraction, high resolution transmission electron microscopy, Brunauer–Emmett–Teller analysis, and so forth to fathom the interlink between observed properties and morphology. High quality superhydrophobic and superhydrophilic films have been generated and the surfaces were modulated by the addition of tri‐block co‐polymer which was found to provide swapping of superhydrophobic nature to superhydrophilic nature. The integration of superhydrophobic, superhydrophilic, photocatalytic and antibacterial properties in the prepared microsphere coatings is a unique achievement and may interest those in the quest for self‐cleaning materials for antibacterial coatings in mitigating surgical site infections, medical implants, coronary stent surfaces, and so forth. Abstract :